THE CONSEQUENCES OF ABORTION RESTRICTIONS FOR ADOLESCENTS’ HEALTHCARE IN GHANA: THE INFLUENCE OF GHANA’S ABORTION LAW ON ACCESS TO SAFE ABORTION SERVICES - Aladago, D. A.; Boakye-Yiadom, A.; Asaarik, M. J.; Aryee, P. A. (UDS International Journal of Development, 2019)
Unsafe abortion accounts for 22,500 to 44,000 maternal deaths worldwide. It is the second leading cause of maternal mortality among adolescent girls (aged 10 – 19 years) worldwide. In Ghana, abortion is more common among adolescents than among other women of reproductive age. Annually, Ghana spends about GH¢37.8 million (US$8.5 million) out of pocket on unsafe abortions, which suggests an increased risk of catastrophic expenditure and poverty for many. Moreover, 11%-30% of maternal deaths in Ghana are due to unsafe abortions and adolescents contribute about 35% of those deaths. Although laws cannot alter adolescents’ need for abortion, restrictive ones are associated with increased unsafe abortions and risk of abortion-related maternal mortality. This qualitative study explored the influence of Ghana’s abortion law on adolescents’ access to safe abortion services using literature review. The search terms “Ghana abortion law” and “adolescent access to induced abortion in Ghana” were used to retrieve relevant articles from PubMed and the Lancet. The study found that although safe abortion is legal in Ghana, it is not available on request which, is a barrier for adolescents. This study concludes that Ghana’s abortion law is restrictive, outdated and does not facilitate adolescents’ access to safe abortion services. The study recommends that the Ghana Health Service and the Ministry of Health advocate for the liberalisation of the law to ensure abortion is legally available on request for adolescents. Keywords: Abortion, Law, Adolescents, Ghana, Health